Ilimaquinone and Ethylsmenoquinone, Marine Sponge Metabolites, Suppress the Proliferation of Multiple Myeloma Cells by Down-Regulating the Level of β-Catenin - Seoyoung Park; Eunju Yun; In Hyun Hwang; Soojin Yoon; Dong-Eun Kim; Ji Seon Kim; MinKyun Na; Gyu-Yong Song; Sangtaek Oh (Marine Drugs, 2014)
Deregulation of Wnt/β-catenin signaling promotes the development of a broad range of human cancers, including multiple myeloma, and is thus a potential target for the development of therapeutics for this disease. Here, we used a cell-based reporter system to demonstrate that ilimaquinone and ethylsmenoquinone (formerly smenorthoquinone), sesquiterpene-quinones from a marine sponge, inhibited β-catenin response transcription induced with Wnt3a-conditioned medium, by down-regulating the level of intracellular β-catenin. Pharmacological inhibition of glycogen synthase kinase-3β did not abolish the ilimaquinone and ethylsmenoquinone-mediated β-catenin down-regulation. Degradation of β-catenin was consistently found in RPMI-8226 multiple myeloma cells after ilimaquinone and ethylsmenoquinone treatment. Ilimaquinone and ethylsmenoquinone repressed the expression of cyclin D1, c-myc, and axin-2, which are β-catenin/T-cell factor-dependent genes, and inhibited the proliferation of multiple myeloma cells. In addition, ilimaquinone and ethylsmenoquinone significantly induced G0/G1 cell cycle arrest and apoptosis in RPMI-8266 cells. These findings suggest that ilimaquinone and ethylsmenoquinone exert their anti-cancer activity by blocking the Wnt/β-catenin pathway and have significant potential as therapies for multiple myeloma.